Management of hypertension and coronary artery disease in vasculitis patients using glucocorticoids - Aygün, Sevda; Kaya, Ergün Barış (Acta Medica, 2024)
Systemic vasculitis is an autoimmune disorder characterized by inflammation and damage to blood vessels, often involving multiple organ systems. Glucocorticoids (GCs) are a cornerstone in managing vasculitis and other rheumatologic conditions due to their potent anti-inflammatory properties, but their use is associated with significant systemic side effects. This review evaluates the cardiovascular (CV) risks associated with glucocorticoid use, focusing on hypertension and atherosclerosis, and highlights strategies for minimizing these risks while managing systemic inflammation in vasculitis patients. Glucocorticoids, despite their efficacy in disease management, contribute to CV complications in a dose- and duration-dependent manner. Hypertension arises through mechanisms such as nitric oxide suppression, renin-angiotensin-aldosterone system activation, and vascular effects. Atherosclerosis is accelerated by endothelial dysfunction, oxidative stress, and inflammation, increasing risks for coronary artery disease and acute CV events. Daily doses exceeding 5 mg of prednisolone are linked to a marked rise in CV risks, even with short-term use. Moreover, systemic inflammation from vasculitis compounds these risks, making it challenging to disentangle GC side effects from the underlying disease pathology. Glucocorticoid therapy requires careful management, prioritizing the lowest effective dose and shortest duration possible. Routine CV risk assessments, blood pressure monitoring, and targeted interventions such as lifestyle modifications and pharmacologic therapies are crucial for mitigating adverse outcomes. Future studies should aim to define “safe” GC thresholds and refine treatment protocols to balance efficacy and safety in vasculitis management.